Yahoo Web Search

  1. So, lim: t →0 [cos( t ) – cos²( t )]/ t = 0 Now, using the Squeeze...x) = lim:x→a h(x) = L, then lim:x→a g(x) = L. So, if g( t ) = [cos( t ) – cos²( t )]/ t , let's find some functions f( t ) and...

    2 Answers · Science & Mathematics · 16/10/2009

  2. assuming T _0 is constant..we can solve the differential equation by setting it up like... ln( T - T _0) = -k* t + C raise to the exponent of e T - T _0 = e^(-k* t )*e^C substitute a lim as t approaches inf...

    1 Answers · Science & Mathematics · 24/03/2011

  3. t ( t ^2 - 2t - 3) = 0 => t ( t +1)( t -3) = 0 => t = 0, -1, 3

    4 Answers · Science & Mathematics · 04/01/2009

  4. ( t -1)^2=2t^2- t -29 . multiply out the left side t ^2 - 2t + 1 = 2t^2- t -29 . move everything to the right 0 = t ^2 + t - 30 . factor 0 = ( t - 5)( t + 6) . set each factor = to 0 and solve t - 5=0 or t = 5 t + 6 = 0 or t = -6

    8 Answers · Science & Mathematics · 24/04/2008

  5. Subtract 2r from both sides to get: T -2r= 2t Divide both sides by 2 to get: T -2r/2 = t Simplify this because the 2 over the other 2 cancel each other out. Answer: t = T -r

    3 Answers · Science & Mathematics · 13/02/2010

  6. Curvature k( t ) = l r'( t ) x r''( t ) l / l r'( t ) l ^3. Now with r( t ) = < 4*sin( t ), 4*sin( t ), -2*cos( t ) > we have r'( t ) = < 4*cos( t ), 4*cos( t ), 2*sin( t ) > and r''( t ) = <...

    2 Answers · Science & Mathematics · 08/03/2013

  7. f( t ) = 20 cos^3( t ) f ' ( t ) = 60 cos^2( t ) * -sin( t ) f ' ( t ) = -60 sin( t ) cos^2( t ) g( t ) = 20 sin^3( t ) g ' ( t ) = 60 sin^2( t ) * cos( t ) g ' ( t ) = -60 cos( t ) sin^2( t ...

    1 Answers · Science & Mathematics · 10/12/2012

  8. Hello, ∫ e^(m t ) sin(ω t ) dt = let's integrate by ...: ∫ u dv = u v - ∫ v du ∫ e^(m t ) sin(ω t ) dt = e^(m t ) (1/ω)[- cos(ω...e^(m t ) cos(ω t ) + (m/ω²) e^(m t ) sin(ω t ) + C hence: ∫ e^(m t ...

    1 Answers · Science & Mathematics · 31/01/2013

  9. T (n) - T (n-1) = log(n). T (n-1) - T (n-2) = log(n-1) T (n-2) - T (n-3) = log(n-2) T (n-3) - T (n-4) = log(n-3...

    1 Answers · Science & Mathematics · 09/02/2016

  10. Expand q( t ) q( t ) = C e^(- t / T ) cos(wt) + D e^(- t / T ) sin(wt...,w are constants. d/dx (term 1) = d/dx [ C e^(- t / T ) cos(wt)] = C e^(- t / T ) (-1/ T ) cos(wt) + C e...

    1 Answers · Science & Mathematics · 18/11/2010

  1. Try asking your question on Yahoo Answers